(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
The article analyzes the impact of implementing competence-based innovative didactic technologies in physics laboratory classes and their contribution to improving educational outcomes. The study involved experimental sessions based on AR/VR technologies, digital twin models, digital laboratory complexes, interactive simulators, and a reflective approach. This experimental methodology contributed not only to strengthening theoretical knowledge but also to preparing students for practical professional activities. The results demonstrated that in the experimental group, the students’ knowledge level increased by an average of 18%, along with significant improvements in independent work, analytical thinking, and the ability to interpret experimental results. This approach plays a significant role in developing 21st-century skills among students.